2014
DOI: 10.1002/aic.14657
|View full text |Cite
|
Sign up to set email alerts
|

A study on the modeling of static pressure distribution of wet gas in Venturi

Abstract: A model for gas-liquid annular and stratified flow through a standard Venturi meter is investigated, using the twophase hydrokinetics theory. The one-dimensional momentum equation for gas has been solved in the axial direction of Venturi meters, taking into consideration the factors including the void fraction, the friction between the two phases and the entrainment in the gas core. The distribution of wet gas static pressure between the two pressure tapings of the Venturi meters has been modeled in the pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The droplets with the Sauter Mean Diameter ( d 32 ) are used to simulate the effects of droplet swarms on the flow; (b) ignore the interactions between the droplets and liquid film; (c) the transient processes are not considered. These assumptions have been validated by the numerical simulations of annular (-mist) flow in the Venturi tube [ 21 , 22 , 23 ]. The results showed that the assumptions were reasonable to simulate the steady characteristics of the flow through the Venturi tube.…”
Section: Numerical Methods and Modelsmentioning
confidence: 99%
“…The droplets with the Sauter Mean Diameter ( d 32 ) are used to simulate the effects of droplet swarms on the flow; (b) ignore the interactions between the droplets and liquid film; (c) the transient processes are not considered. These assumptions have been validated by the numerical simulations of annular (-mist) flow in the Venturi tube [ 21 , 22 , 23 ]. The results showed that the assumptions were reasonable to simulate the steady characteristics of the flow through the Venturi tube.…”
Section: Numerical Methods and Modelsmentioning
confidence: 99%
“…Equations (3) and (4) are referred to as the general model because its basic form can be theoretically derived. For example, if the pressure drop of convergent section is assumed to be dominated by the accelerate pressure drop [ 26 ], then the differential form of the pressure drop can be written as: …”
Section: Theoretical Modelmentioning
confidence: 99%
“…Figure 10 shows plots of the experimental and calculated two-phase mass flow rate obtained from the homogeneous model and the correlations of Chisholm, 4 James 28 and Zhang et al 30 it is seen from Figure 10(a) and as expected, the homogeneous flow model is less accurate than the others, and the accuracy decreases more with increasing the total two-phase mass flow rate which is due to the effect of the slip ratio. Figure 10 In order to quantify the deviation between the experimental two-phase mass flow rate data and that from correlations summarized in Table 3, the root mean square (RMS) deviation and the mean relative absolute error (ABE) were calculated as given in equations ( 23) and (25).…”
Section: Assessment Of the Two-phase Mass Flow Correlationsmentioning
confidence: 99%
“…The given correlation is fitted by experimental data of wet gas pressure drop in a Venturi meter positioned horizontally. Peining et al 25 developed a model for calculating axial static pressure in Venturi meter using the hydrodynamics theory. The wet gas annular flow was the interest of their study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation